Foreign And Local Experience In Developing The Entrepreneurial Competencies Of Future Primary Class Teachers On The Basis Of Social Partnership - I.A. Adkhamova (Open Academia, 2023)
The article talks about ways to develop entrepreneurship and entrepreneurship competencies of future primary school teachers based on local and foreign experiences.
Keywords: business; entrepreneurship; competence